50 Years of Publication: A Document Analysis of Social Justice in the Educational Considerations Corpus - Tracey Conway; Nelofar Khamisani; Vajiheh Shahsavari; Ernestina Wiafe (Educational Considerations, 2024)
The purpose of this research article is to explore how social justice in education has evolved over the past 50 years of peer-reviewed article publications in Kansas State University College of Education’s academic journal, Educational Considerations. The research sought to unveil how social justice in education has evolved over the past 50 years based on publications in Educational Considerations. The study utilized a qualitative research approach, specifically adopting a document analysis methodology. This research drew its data from peer-reviewed articles published in Educational Considerations spanning from 1973 to 2023. Literature not originally found in Educational Considerations—but relevant to the research objectives—was only incorporated during the analysis and discussion stages. Thematic data analysis was used to make sense of the collected data. Nancy Fraser’s three-dimensional social justice theory served as the underlying framework in which the articles surrounding social justice in education from each era of the journal Educational Considerations were analyzed and discussed. The findings show that articles published in this journal remain relevant in addressing contemporary educational challenges, ensuring that the pursuit of educational equity endures. In conclusion, the journal’s 50-year history reflects its dedication to promoting equitable education and contributing to the field of education.
Keywords: Social justice in education; document analysis; and Educational Considerations